UK DRAFFT - a randomised controlled trial of percutaneous fixation with kirschner wires versus volar locking-plate fixation in the treatment of adult patients with a dorsally displaced fracture of the distal radius. - Costa, M; Achten, J; Parsons, N; Rangan, A; Edlin, R; Brown, J; Lamb, S (BioMed Central, 2011)
BACKGROUND: Fractures of the distal radius are extremely common injuries in adults. However, the optimal management remains controversial. In general, fractures of the distal radius are treated non-operatively if the bone fragments can be held in anatomical alignment by a plaster cast or orthotic. However, if this is not possible, then operative fixation is required. There are several operative options but the two most common in the UK, are Kirschner-wire fixation (K-wires) and volar plate fixation using fixed-angle screws (locking-plates). The primary aim of this trial is to determine if there is a difference in the Patient-Reported Wrist Evaluation one year following K-wire fixation versus locking-plate fixation for adult patients with a dorsally-displaced fracture of the distal radius. METHODS/DESIGN: All adult patients with an acute, dorsally-displaced fracture of the distal radius, requiring operative fixation are potentially eligible to take part in this study. A total of 390 consenting patients will be randomly allocated to either K-wire fixation or locking-plate fixation. The surgery will be performed in trauma units across the UK using the preferred technique of the treating surgeon. Data regarding wrist function, quality of life, complications and costs will be collected at six weeks and three, six and twelve months following the injury. The primary outcome measure will be wrist function with a parallel economic analysis. DISCUSSION: This pragmatic, multi-centre trial is due to deliver results in December 2013. TRIAL REGISTRATION: Current Controlled Trials ISRCTN31379280 UKCRN portfolio ID 8956.